Development of an Intervention to Support the Reproductive Health of Cambodian Women Who Seek Medical Abortion: Research Protocol - Oreglia, Elisa (JMIR Res Protoc, 2020)
BACKGROUND: In Cambodia, abortion has been legally permitted on request during the first trimester of pregnancy since 1997. However, although there has been an increase in the percentage of women having induced abortion and medical abortion, there has also been a decrease in the percentage of women who say they received help from a health worker with their abortion. These data point toward the demedicalization of abortion, and although medical abortion has been shown to be safe, there are concerns about safety, given the variety of available products and counseling provided. These concerns are particularly relevant for female factory workers, who typically come from rural areas where access to good health care and information about reproductive health care is limited. OBJECTIVE: This study aims to understand the reproductive health needs of female Cambodian garment factory workers after medical abortion from a multidisciplinary and mixed-methods perspective, focusing on how they seek and share medical abortion- and health-related information; how they use their mobile phones for this and other purposes; what cultural challenges exist around reproductive health; and how they might be magnified or mitigated by mobile phones, linguistic challenges around health care, and mobile phone use. The main purpose of this study is to combine multidisciplinary methods, theories, and expertise to gain new, culturally grounded insights into family planning and medical abortion in Cambodia, but the findings could help inform the development of a relevant intervention to support comprehensive postabortion care. METHODS: The methods proposed are interviews and participant observation among factory workers, health providers, and mobile phone providers; a linguistic analysis of relevant data (interview transcripts, web-based sources, and other fieldwork materials); and digital methods to understand what kind of information about medical abortion exists on the web in Cambodia and how it is accessed by the targeted population. RESULTS: The data collection part of the project will end on December 31, 2020. The team conducted 67 semistructured interviews with female factory workers, women who sought a medical abortion, health providers, and mobile phone providers; participant observation with factory workers and health providers; and an analysis of YouTube and Facebook to understand what kind of information is available, who creates it, and how it is used. The team is currently performing data analysis, and the findings are clustered around (1) the use of mobile phones and digital resources for health-related and medical abortion-related information, (2) the experience of medical abortion care, and (3) the development of an intervention through edutainment videos. CONCLUSIONS: The project highlights both the widely untapped potential of using digital platforms (especially YouTube and Facebook) to distribute accurate information on medical abortion and the challenges in providing individual information via mobile phones while respecting individuals’ privacy. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): DERR1-10.2196/17779